2014
DOI: 10.1073/pnas.1418087111
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral small vessel disease-related protease HtrA1 processes latent TGF-β binding protein 1 and facilitates TGF-β signaling

Abstract: Significance Cerebral small vessel disease (SVD) is a major cause of stroke and dementia. Hereditary forms, such as cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL), may provide insights into key molecular mechanisms and pathways. The serine protease HtrA1, whose activity is impaired in CARASIL, has been proposed to attenuate TGF-β signaling leading to increased pathway activity in diseased arteries. We analyzed HtrA1-deficient mouse brain tissue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 39 publications
(48 reference statements)
3
111
0
Order By: Relevance
“…To advance our understanding of the mechanisms underlying HtrA1 deficiency, we used dermal fibroblasts from CARASIL patients and Htra1 knockout mice as experimental systems (2). We agree with Liu et al that findings from fibroblasts might or might not fully reflect the physiological processes occurring in a vessel wall and that alterations in other cell types such as endothelial and vascular smooth muscle cells (VSMCs) certainly contribute to CARASIL vessel pathology.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…To advance our understanding of the mechanisms underlying HtrA1 deficiency, we used dermal fibroblasts from CARASIL patients and Htra1 knockout mice as experimental systems (2). We agree with Liu et al that findings from fibroblasts might or might not fully reflect the physiological processes occurring in a vessel wall and that alterations in other cell types such as endothelial and vascular smooth muscle cells (VSMCs) certainly contribute to CARASIL vessel pathology.…”
supporting
confidence: 62%
“…Nevertheless, fibroblast cultures have been successfully used in the past to study TGF-β dysregulation in other vascular disorders, demonstrating their usefulness in the elucidation of disease-relevant mechanisms (3). Moreover, HtrA1-dependent changes in TGF-β activity were observed not only in fibroblasts but also in mouse brains arguing for their presence in other cell types (2).…”
mentioning
confidence: 93%
“…The protein is implicated as a tumor suppressor and shown to play an important role in extracellular matrix remodeling during placental development and arthritis (Chien et al., 2004; Grau et al., 2006; Nie et al., 2006). It cleaves and inhibits TGF beta, and several extracellular matrix proteins, including fibronectin and amyloid precursor protein (Beaufort et al., 2014; Grau et al., 2005; Oka et al., 2004). Also, when HTRA1 is overexpressed in mice, the elastic network of extracellular matrix becomes fragmented between the RPE and the choroid (Vierkotten, Muether & Fauser, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…101 Contrasting these findings, a more recent study in HTRA1-deficient mice and CARASIL patient cells revealed a facilitating role of HtrA1 on the TGF-pathway. 35 The same study showed that LTBP-1 is a substrate for HtrA1. These findings suggest that HtrA1-mediated proteolysis of LTBP-1 promotes release of TGF-from the ECM ( Figure 2B).…”
Section: Cerebral Autosomal Recessive Arteriopathy With Subcortical Imentioning
confidence: 93%
“…Initially thought to be restricted to the Japanese population, in recent years an increasing number of CARASIL cases has been reported from outside Japan indicating a more widespread distribution of this disorder. [33][34][35] The COL4A1/A2-related angiopathies (OMIM: 607595; 614519) represent highly penetrant multisystem disorders with heterogeneous phenotypes. 36 Heterozygous mutations in COL4A1 encoding the 1 chain of type IV procollagen were initially identified as a cause for porencephaly, an infantile neurologic disorder associated with hemorrhages and hemiplegia.…”
Section: Mendelian Forms Of Small Vessel Diseasementioning
confidence: 99%